2018
DOI: 10.1080/07853890.2018.1538565
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intravenous esmolol for cardiac protection in non-cardiac surgery. A systematic review and meta-analysis

Abstract: Running head: Esmolol for cardiac protection after surgery surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
1
9
0
2
Order By: Relevance
“…A meta-analysis showed that esmolol seems to be beneficial for the prevention of perioperative myocardial ischaemia. 17 Another study proved that esmolol 0.5 mg/kg combined with nicardipine 20 ug/kg during rapid-sequence induction can effectively reduce cardiovascular response. 18 Esmolol can also be used for controlled hypotension in various operations such as functional endoscopic sinus surgery (FESS), tympanoplasty and laparoscopic surgeries.…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis showed that esmolol seems to be beneficial for the prevention of perioperative myocardial ischaemia. 17 Another study proved that esmolol 0.5 mg/kg combined with nicardipine 20 ug/kg during rapid-sequence induction can effectively reduce cardiovascular response. 18 Esmolol can also be used for controlled hypotension in various operations such as functional endoscopic sinus surgery (FESS), tympanoplasty and laparoscopic surgeries.…”
Section: Discussionmentioning
confidence: 98%
“…Hızlı başlangıç ve kısa etki süreli β-1 selektif ilaç olan esmolol, spesifik hemodinamik hedefe uygun ilaç titrasyonu ile ilaç dozunun bireyselleştirilmesine izin vermektedir. Böylece ilaca bağlı bradikardiyi ve hipotansiyonu en aza indirerek kardiyak koruma sağlayabilmektedir (18). Yaptığımız çalışmamızda hedef kalp atım hızına ulaşmak için intraoperatif dönemde ve postoperatif 48 saat titre edilerek esmolol uygulaması yapılmıştır.…”
Section: Discussionunclassified
“…Викликає зацікавленість медичної спільно ти використання есмололу для кардіопротекції під час хірургічних втручань, як у кардіохірургії, так і опера тивних втручань інших локалізацій. Доведено, що ес молол зменшує постопераційну міокардіальну ішемію, знижує ризик великих серцевих ускладнень протягом 30 діб після втручання завдяки редукції гемодинаміч ної нестабільності [13,14,15].…”
Section: вступunclassified